Otra narrativa de la Transición : las crónicas de sucesos de Margarita Landi en la revista Interviú - Víctor J. Ortega Muñoz (Amnis)
There are multiple discourses that converge on the Spanish public scene during the Transition period. Beyond extensively studied political issues and official narratives, we want to direct the focus of attention to less accustomed places : the information about events published in the Interviú magazine during the time of the pioneer of the crime scene, Margarita Landi. This means of communication assumed from the beginning the new political and moral freedoms that arise with the Transition towards democracy, combining political information and denunciation with eroticism, groundbreaking elements that add up to obtain a considerable reader base and become one of the media reference. Within its configuration, the inclusion of event information represents a basic prop ; The commitment decided by this section will be confirmed in 1980 with the signing of the star reporter of El Caso, Margarita Landi, a proven professional, who enjoys the approval of the readers. Through his sharp gaze and going through the examples of the breakdown of normality collected in the pages of Interviú, we approach the society of the moment and its problems.